Ethical Values in Narit Maja as Teaching Material for Pancasila and Civic Education (PPKn) to Develop Students’ Character - Herawati, Cut; Muksalmina, Muksalmina; Muhammad, Muhammad; Chairullah, Muhammad; Yulis, Sari; Furqan, Muhammad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Character education is a core mandate of Indonesia’s national education system, yet classroom practices often prioritize cognitive achievement over value internalization. Specific Background In Pancasila and Civic Education learning, especially in Lhokseumawe City, teaching remains largely normative and theoretical, with limited integration of students’ socio-cultural realities. Knowledge Gap Although Acehnese local wisdom contains rich ethical teachings, Narit Maja as an oral tradition has not been systematically utilized as contextual teaching material in Civic Education. Aims This study aims to explore the ethical values embedded in Narit Maja and examine their relevance for integration into Pancasila and Civic Education learning. Results Using a descriptive qualitative ethnopedagogical approach, the study identifies values of honesty, deliberation, mutual cooperation, responsibility, and patriotism within Narit Maja that align with the dimensions of the Pancasila Student Profile. The findings also reveal structural and practical challenges, including limited regulations, insufficient documented materials, and institutional sectoral constraints, while highlighting digitalization as a strategic pathway. Novelty This study positions Narit Maja as a culturally grounded source of Civic Education content that bridges national curriculum objectives with Acehnese socio-cultural contexts. Implications Integrating Narit Maja into Civic Education supports contextual character formation, strengthens students’ cultural identity, and offers a sustainable approach to aligning national character education with local wisdom in Lhokseumawe City. Highlights: Acehnese oral expressions contain structured ethical principles aligned with national character frameworks. Contextual learning rooted in local culture addresses gaps between normative curriculum and student realities. Digital-based materials provide a feasible pathway for preserving oral traditions in formal schooling contexts. Keywords: Narit Maja, Civic Education, Character Education.